Patulin and citrinin production by Penicillium expansum strains isolated from grapes - Abrunhosa, Luís (2000)
Penicillium expansum strains were isolated from grapes from the Douro wine region, and assayed for their capacity of producing patulin and citrinin, which are mycotoxins, on two media. The presence in grapes of this species can cause spoilage during processing and these mycotoxins may be produced. A total of 51 strains were assayed and all strains produce citrinin on YES medium, but only one strain was able to produce it when grown in a grape juice medium (GJM). Patulin was produced by 20% of strains on YES, and 70% produce it on GJM. These data will be presented and discussed.